Isolamento e identificação de microrganismos produtores de hidrogênio a partir do glicerol residual - Poleto, Liliane (My University, 2015)
One of the major challenges for the coming years is to develop alternative forms of production for sustainable energy. The biodiesel is positioning itself as an option for the replacement of fossil fuels. Its production is by transesterification between a fat and a monoalcohol, releasing glycerol, which corresponds to 10% of the volume of the reaction. Large increases in the production of biodiesel result in proportional amounts of crude glycerol.Studies have shown that strict anaerobic and fermentative bacteria are able to produce hydrogen, a fuel of high energy value, which does not generate polluting gases, during its burning. Given the importance of increasing the added value-added of crude glycerol, the purpose of this study was to isolate and identify by molecular techniques, bacteria present in sewage sludge from waste treatment plants, it is capable of producing hydrogen using crude glycerol of biodiesel industry, as a carbon source. The samples were subjected to thermal shock to eliminate hydrogenotrophic bacterias, grown in the medium containing glycerol under anaerobic conditions and analyzed to produce hydrogen. Were identified by sequencing of the 16S rRNA gene , 15 bacterial species able to grow in medium with glycerol, and from these, nine showed the ability of hydrogen production, corresponding to Enterobacter ludwigii, Shigella sonnei, Bacillus licheniformis, Bacillus amyloliquefaciens, Staphylococcus warneri, Alcaligenes faecalis, Bacillus subtilis, Bacillus atrhopheus and Citrobacter freundii. The Bacillus amyloliquefaciens isolate showed higher yield in the production of hydrogen , with values of 0.50±0.20 mol H2/mol of glycerol, using the enriched medium with 1.5% crude glycerol. In addition, BLAST analysis were performed to check the presence of genes HycC, HycE, HycF, HyfC, HyfF and HyfH related to hydrogen production. This study was developed using microorganisms of genus Bacillus, since, among the isolated microorganisms, only the Bacillus have complete DNA sequencing available. It was found that B. amyloliquefaciens, B. licheniformis and B. artrophaeus do not have the specific genes analyzed, but these genes have similarity with other genes and proteins that appear to perform roles in the transport of hydrogen to outside the cell. The results indicate that there is a great potential for the selection of bacteria producing hydrogen in the effluents evaluated, that are able to metabolize crude glycerol with the generation of hydrogen as a fuel for renewable energy.
Um dos grandes desafios para os próximos anos é desenvolver alternativas de produção para energias sustentáveis. O biodiesel vem se posicionando como uma opção para a substituição dos combustíveis fósseis. Sua produção se dá pela transesterificação entre uma gordura e um monoálcool, liberando glicerol, que corresponde a 10% do volume da reação. Grandes incrementos na produção de biodisel resultarão em volumes proporcionais de glicerol residual. Estudos têm mostrado que bactérias anaeróbias estritas e bactérias fermentativas são capazes de produzir hidrogênio, um combustível de alto valor energético, que não gera gases poluentes durante a sua queima. Visto a importância de aumentar o valor agregado do glicerol residual, o presente trabalho teve como objetivo isolar e identificar por técnicas moleculares, bactérias presentes em lodos de estações de tratamento de resíduos, capazes de produzir hidrogênio utilizando glicerol residual da indústria de biodiesel como fonte de carbono. As amostras foram submetidas a choque térmico para eliminação de bactérias hidrogenotróficas, crescidas em meio contendo glicerol em condições de anaerobiose e analisadas para a formação de hidrogênio. Foram identificadas por sequenciamento do gene 16S rRNA, quinze espécies bacterianas capazes de crescer em meio com glicerol, sendo que destas nove apresentaram capacidade de produção de hidrogênio, correspondendo a Enterobacter ludwigii, Shigella sonnei, Bacillus licheniformis, Bacillus amyloliquefaciens, Staphylococcus warneri, Alcaligenes faecalis, Bacillus subtilis, Bacillus atrophaeus e Citrobacter freundii. Os isolados de Bacillus amyloliquefaciens mostraram maior rendimento na produção de hidrogênio com valores de 0,50±0,20 mol H2/mol de glicerol, utilizando o meio enriquecido com 1,5% de glicerol residual. Adicionalmente, foi realizada análise de BLAST para verificar a presença dos genes HycC, HycE, HycF, HyfC, HyfF e HyfH relacionados à produção de hidrogênio. Este estudo foi desenvolvido utilizando apenas os microrganismos do gênero Bacillus, uma vez que, dentre os microrganismos isolados, apenas os Bacillus apresentam sequenciamento completo disponível na rede de bioinformática. Foi verificado que B. amyloliquefaciens, B. licheniformis e B. artrophaeus não possuem os genes específicos analisados, mas estes genes possuem similaridade com outros genes e proteínas que parecem desempenhar funções no transporte de hidrogênio para exterior da célula. Os resultados indicam que existe um grande potencial para a seleção de bactérias produtoras de hidrogênio nos efluentes avaliados que são capazes de metabolizar o glicerol residual com a geração de hidrogênio, como combustível de energia renovável.
Keywords: Biocombustíveis; Hidrogênio como combustível; Biodiesel; Microorganismos; Biofuels; Hydrogen as fuel; Biodiesel fuels; Microorganisms